Exposure to perfluoroalkyl substances in early pregnancy and the risk of hypertensive disorders of pregnancy: A nested case-control study in Guangxi, China. (February 2022) - Liu, Bihu; Wei, Bincai; Mo, Meile; Song, Yanye; Tang, Chuanqiao; Tang, Peng; Guo, Xiaojing; Tan, Chao; Liu, Shun; Huang, Dongping; Qiu, Xiaoqiang
Abstract: Background: Previous epidemiological studies have examined the associations between exposure to perfluoroalkyl substances (PFASs) and the risk of hypertensive disorders of pregnancy (HDP). However, these studies have drawn discrepant conclusions and have some limitations. Methods: A nested case-control study was conducted with the Guangxi Zhuang Birth Cohort (GZBC), a prospective, ongoing birth cohort that was implemented in Guangxi, China, in June 2015. Maternal serum concentrations of nine PFASs were measured using ultra-high-performance liquid chromatography-tandem mass spectrometry (UPLC-MS). The associations between PFAS exposure and the risk of HDP were assessed using logistic regression (single-exposure), weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR) models. Results: A total of 136 HDP cases and 408 controls were enrolled in this study. In logistic regression models, perfluoroundecanoic acid (PFUnA), perfluorooctane sulfonate (PFOS), perfluorononanoic acid (PFNA) and perfluorobutanesulfonic acid (PFBS) were positively associated with HDP, while perfluorohexane sulfonate (PFHxS) was inversely associated with HDP. In the BKMR analysis, the joint effect of PFASs was positively associated with HDP. PFOS and PFBS showed positive trends, while PFHxS and PFHpA showed inverse trends. In WQS regression analysis, we calculated two WQS indices that were estimated using constraints in both the positive and negative directions of effects. Both WQS indices were significantly associated with HDP (OR: 2.663, 95% CI: 1.795–3.951; OR: 0.338, 95% CI: 0.229–0.499, respectively). PFBS, PFOS and PFUnA had significant weights in the positive effect direction; PFHxS, perfluoroheptanoic acid (PFHpA) and perfluorododecanoic acid (PFDoA) had significant weights in the negative effect direction. Conclusion: Considering all model results, we found that combined exposure to nine PFASs had a positive effect on the development of HDP. Moreover, PFOS and PFBS were positively associated with the HDP risk, while PFHxS and PFHpA were negatively associated with the HDP risk in women in Guangxi, China. Graphical abstract: Image 1 Highlights: A nested case-control study was conducted. Logistic regression, BKMR model and WQS regression model. The joint effect of PFASs was significantly positively associated with HDP. PFOS and PFBS were positively associated with the risk of HDP. PFHxS and PFHpA were negatively associated with the risk of HDP.